Proposta de escala de mensuração do sucesso do projeto - Fernandes, Gabriel Francisco Pistillo (2022)
This thesis deals with the analysis of scientific and technical production related to ways of quantitatively measuring the project success and discussions about their effectiveness and potential developments. There are several studies on the measurement of success in projects, however, an overview of the concept of project success and the current panorama of construct measurement has not yet been extensively developed. In this thesis, after examining the literature, a scale is proposed for measuring success in projects through three studies; it is also estimated the derivation of a technological product related to the process of measuring success in projects. The general objective is to analyze the measurement of project success from the perspective of the literature published in the main project management journals in the last five years. The generation of a scale is justified by the fragmentation of the field and by weaknesses of perception scales frequently used, which direct the evaluation of success to project managers, without directly capturing the other dimensions of success in projects despite recognizing them. The first study, bibliometric, dealt with the understanding of the field and the state of the art about project success more broadly. The second study, a systematic literature review, sought to capture and understand the current scales of project success measurement to support collecting scales with good evaluation and wide use for scales combination. In the third study, a qualitative-quantitative effort was undertaken to create a combination and application scale for exploratory evaluation of factors. It is expected that from study three, a technological product will be developed, related to the measurement process developed in the thesis, potentially patentable.